Three Crises in Search of a Policy - Yaphe, Judith (Tufts Archival Research Center, 2005)
Volume 25, Issue 1. Winter Yaphe discusses the complex challenges faceing the new U.S. president in the Middle East, with a focus on Iran, Iraq, and the Israeli-Palestinian conflict.